2021
DOI: 10.3389/fmars.2021.759919
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Mollusks: Research Progress, Current Contamination Status, Analysis Approaches, and Future Perspectives

Abstract: Plastic fragments < 5 mm, known as microplastics (MPs), are ubiquitously present in the marine environment. Research on MPs pollution has gradually shifted from field investigations to laboratory studies. With the rapid growth of plastic consumption and the prevalence of aquaculture products, studies on marine MPs have focused on key marine species, such as mollusks. This review summarizes the recent knowledge including 77 important relevant literatures (from 2010 to 2021) on MPs contamination in mollus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 90 publications
(81 reference statements)
1
6
0
2
Order By: Relevance
“…Out of 40 samples observed, microplastics were observed in all samples of G. erosa (100 %), and only one sample of T. telescopium was observed without microplastic particles. The result of this study supported the results of many studies of microplastic in molluscs that is alarming as an ecological and health risk [33]. Fiber was found the most in all samples of both species, followed by fragment, film and beads (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Out of 40 samples observed, microplastics were observed in all samples of G. erosa (100 %), and only one sample of T. telescopium was observed without microplastic particles. The result of this study supported the results of many studies of microplastic in molluscs that is alarming as an ecological and health risk [33]. Fiber was found the most in all samples of both species, followed by fragment, film and beads (Fig.…”
Section: Resultssupporting
confidence: 89%
“…2). The domination of fiber has been the result of many studies since this type of microplastics is ubiquitous in the marine environment [9], [33], [34]. It has been observed that fiber come from domestic activities such as washing product of textile or fabric [5] and also fisheries activities [3].…”
Section: Resultsmentioning
confidence: 99%
“…Contaminant accumulation has been reported in crustacean hepatopancreas [334][335][336] and in the skin, viscera, bones, and scales of fish [337][338][339][340][341]. Mollusks also accumulate toxicants [342][343][344][345], with the digestive glands and gills of hard-shelled animals representing preferential accumulation sites [346][347][348]. The presence of marine biotoxins may represent a very concrete challenge for the use of marine animal co-products.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Gambar 1. Kerang Kepah (Polymesoda erosa) yang ditemukan di wilayah pesisir, Desa Sungai Nibung Menurut Morton (1976) (Melinda et al, 2015;Wang et al, 2021) yang dapat mengakumulasi logam berat dari lingkungan sekitar (Alyani et al, 2017;Dharmadewi, 2020). Oleh karena itu, kerang kepah dapat digunakan sebagai bioindikator kualitas perairan (Cruz et al, 2020;Azis et al, 2021;Yanova et al, 2022).…”
Section: Hasil Dan Pembahasan Jenis Bivalvia Yang Ditemukan DI Wilaya...unclassified